Time and chronology in creation narratives - Kilgallon, Silvie; Mitchell, Fiona (Routledge monographs in classical studies, 2025)
"This book explores the ways in which the origins of time, of the gods, and processes associated with time were conceptualised in antiquity, examining a variety of ancient sources from across the ancient world and addressing issues surrounding the sources themselves. Time is a key framework through which we understand the world around us. Shared structures to measure the passage of time reveal certain cultural and societal values, while time's less concrete forms are evident across art and literature. This volume examines how the tangible and intangible, direct and complex representations of time are used in ancient sources. The chapters in this book are written by scholars whose work focuses on India, Assyria, Greece, and Rome. Their analyses explore poetic and mythological narratives, philosophical discourse, and representations of the divine, allowing us to see how ideas about time and chronology reveal various cultural understandings of our world. Accessibly written, this volume enables scholars from a variety of disciplines to engage effectively with each chapter. Time and Chronology in Creation Narratives offers a fascinating interdisciplinary collection suitable for scholars working in ancient literature, philosophy, and religion across Classics, Ancient History, Indology, and Near Eastern Studies"--